2020
DOI: 10.21203/rs.3.rs-40632/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

County-Level Longitudinal Clustering of COVID-19 Mortality to Incidence Ratio in the United States

Abstract: Abstract Background: As of June 3, 2020, the mortality to incidence ratio (MIR) of COVID-19 was 5.8%. We utilized a longitudinal model-based clustering system based on the disease trajectories over time.Methods: County-level COVID-19 cases and deaths (March-June 2020), and a set of potential risk factors were collected for 3050 U.S. counties. We used growth mixture models to identify clusters of counties exhibiting similar C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 64 publications
(85 reference statements)
0
6
0
Order By: Relevance
“…Variables in the symbol column correspond to Equation 1 . INDEX DOMAIN INDICATOR SOURCE LEVEL SYMBOL NOTES REFERENCES SEVI 1 Jobseekers Allowance Rate NOMIS 1 MSOA v 1 6 , 11 , 12 1 Rank of Index of Multiple Deprivation (IMD) Gov.uk 2 LSOA v 2 Averaged over LSOAs within MSOA 6 , 12 , 13 , 14 , 15 1 Long term unemployment, per 100 population of working age† PHE Fingertips 6 MSOA v 3 6 , 11 , 12 , 16 2 Proportion population over 65 ONS 4 MSOA v 4 17 , 18 2 Ethnicity (% non-white population) * NOMIS 1 MSOA v 5 5 , 19 , 20 2 Household overcrowding* Gov.uk 2 LSOA v 6 Averaged over LSOAs within each MSOA 2 , 6 , 21 …”
Section: Methodsmentioning
confidence: 99%
“…Variables in the symbol column correspond to Equation 1 . INDEX DOMAIN INDICATOR SOURCE LEVEL SYMBOL NOTES REFERENCES SEVI 1 Jobseekers Allowance Rate NOMIS 1 MSOA v 1 6 , 11 , 12 1 Rank of Index of Multiple Deprivation (IMD) Gov.uk 2 LSOA v 2 Averaged over LSOAs within MSOA 6 , 12 , 13 , 14 , 15 1 Long term unemployment, per 100 population of working age† PHE Fingertips 6 MSOA v 3 6 , 11 , 12 , 16 2 Proportion population over 65 ONS 4 MSOA v 4 17 , 18 2 Ethnicity (% non-white population) * NOMIS 1 MSOA v 5 5 , 19 , 20 2 Household overcrowding* Gov.uk 2 LSOA v 6 Averaged over LSOAs within each MSOA 2 , 6 , 21 …”
Section: Methodsmentioning
confidence: 99%
“…We assume zero international migration, and do not include marriage rates. Second, we do not consider within-country heterogeneity or clustering of excess mortality within groups or families, which means that our estimates are likely a lower bound for excess bereavement [13]. Third, we assume demographic stability before 1950 in our simulations: this is a necessary assumption since reliable historical demographic data is not available for all countries studied.…”
Section: Methodsmentioning
confidence: 99%
“…Other works have used clusters to analyze the Covid-19 impact on counties across the United States [9][10][11]. The authors clusterized counties with similar Covid-19 fatality levels and concluded that heart disease and cancer are the risk factors that most increase the Covid-19 fatality rate [9]. Combining unsupervised and supervised learning, a study showed that the risk of infection and death by Covid-19 in US counties are positively associated with the poverty rate, percentage of people without health insurance, percentage of non-white people, smoker percentage, ICU bed rate, and population density [10].…”
Section: Sociodemographic Factors Associated Withmentioning
confidence: 99%
“…In the literature, some studies identified patterns of the Covid-19 impact in different countries [4][5][6][7][8]. Other works have used clusters to analyze the Covid-19 impact on counties across the United States [9][10][11]. The authors clusterized counties with similar Covid-19 fatality levels and concluded that heart disease and cancer are the risk factors that most increase the Covid-19 fatality rate [9].…”
Section: Sociodemographic Factors Associated Withmentioning
confidence: 99%